THE EFFECTIVENESS OF IMPLEMENTING THE ISO 9001:2015 QUALITY MANAGEMENT SYSTEM IN SUPPORTING CUSTOMER SERVICE AT PT. PELINDO TERMINAL PETIKEMAS - Oggy Octaviani Patmiko; Nurita Andriani (Universitas Putera Batam, 2023)
Implementing a consistent quality management system has a substantial impact on service quality and customer satisfaction. TOP Management plays a crucial part in creating the system to assess the company's level. This research aims to analyze the effectiveness of PT. Pelindo Terminal Petikemas's implementation of the ISO 9001:2015 quality management system in providing customer service at its headquarters. This type of study employs descriptive qualitative research methodology, where primary data and secondary data are employed to acquire the data required to present an overview of the research. Obtaining primary data through interviews and direct observation. Secondary data comprises of profiles of PT. Pelindo Terminal Petikemas, Human Resource Conditions, and Quality Management in customer support services.According to the findings of the study, the implementation of the ISO 9001: 2015 quality management system to support customer service was nearly ideal. The results of a survey of service providers demonstrate that employees of PT. Pelindo Terminal Petikemas understand and have implemented an ISO 9001:2015 quality management system in supporting customer services. As a result, PT. Pelindo Terminal Petikemas has created a comfortable and safe environment, beginning with port equipment, precise and fast loading and unloading times, and friendly service.